2019
DOI: 10.1108/jamr-01-2018-0008
|View full text |Cite
|
Sign up to set email alerts
|

Understanding service quality: insights from the literature

Abstract: Purpose The purpose of this paper is to review the service quality (SQ) literature in order to understand issues involved in its conceptualization and operationalization. Design/methodology/approach The paper uses systematic literature review method. The unit of analysis is peer-reviewed journal articles published during 1984 to 2017. Findings Findings suggest manufacturing, banking, information technology, higher education, healthcare are the top sectors contributing to the SQ literature. More than 60 mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
43
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(46 citation statements)
references
References 195 publications
2
43
0
1
Order By: Relevance
“…Also, the results from the CFA confirmed the connotation that the three factor model in Jordan and the four factor model in Yemen have better fit indices than the original five factor model. These findings are consistent with the extent literature on the topic, which found SERVQUAL to be three or four dimensional constructs rather than a five dimensional one [43] [88], which found that the five dimensions are different across service industries and countries.…”
Section: Resultssupporting
confidence: 90%
See 3 more Smart Citations
“…Also, the results from the CFA confirmed the connotation that the three factor model in Jordan and the four factor model in Yemen have better fit indices than the original five factor model. These findings are consistent with the extent literature on the topic, which found SERVQUAL to be three or four dimensional constructs rather than a five dimensional one [43] [88], which found that the five dimensions are different across service industries and countries.…”
Section: Resultssupporting
confidence: 90%
“…This study has contributed to marketing literature by conducting a comparative study of service quality dimensions and their impact on customer satisfaction on the mobile telecommunications markets of Jordan and Yemen.Theoretically, our study has responded to important requests from e-service quality researchers[43] [64] who indicated that previous studies on e-service quality differences are limited, and the measurement scales of SERVQUAL and SERVPERF have been introduced and verified in Europe and North America. This study builds on existing discussions about SERVQUAL in developed M. Akroush et al DOI: 10.4236/tel.2019.92021 287 Theoretical Economics Letters economies, providing different perspectives on Mobile Telecommunications in emerging economies by comparing quality dimensions between Jordanian and Yemeni customers.…”
mentioning
confidence: 87%
See 2 more Smart Citations
“…Human element is the most important factor while determining the quality of service delivered as the customer and provider are continuously in touch throughout the service delivery process. Human involvement adds variability to the service quality, and thus, it is imperative to monitor it regularly (Prakash, 2019).…”
Section: Perceived Service Qualitymentioning
confidence: 99%